Puppy Mudge takes a bath - Rylant, Cynthia (New York : Simon & Schuster Books for Young Readers, 2002)
When his puppy Mudge gets dirty, Henry has some trouble giving him a bath.
Keywords: Dogs -- Fiction; Baths -- Fiction